Modulation of initial leftward bias in visual search by parietal tDCS. - Laurie Geers; Valérie Dormal; Mario Bonato; Yves Vandermeeren; Nicolas Masson; Michael Andres (PLoS ONE)
Transcranial direct current stimulation (tDCS) has the potential to modulate spatial attention by enhancing the activity in one hemisphere relative to the other. This study aims to inform neurorehabilitation strategies for spatial attention disorders by investigating the impact of tDCS on the performance of healthy participants. Unlike prior research that focused on visual detection, we extended the investigation to visual search and visual imagery using computerized neuropsychological tests. Forty-eight participants had to actively search for targets in space (visual search) and notice differences between two mental images (visual imagery). Anodal stimulation was administered over the left parietal cortex for half of the participants and over the right parietal cortex for the other half. The results showed that tDCS modulated spatial attention in visual search but not in visual imagery. In the sham condition, visual search was characterized by a leftward bias in the selection of the first target and a left asymmetry in the overall spatial distribution of cancelled targets. Parietal tDCS modulated the initial leftward bias, enhancing it (more lateral) during right anodal stimulation and reducing it (more central) during left anodal stimulation. However, this effect was not reflected in the spatial distribution of the cancelled targets. The overall visual search performance marginally improved during right anodal stimulation, as evidenced by a greater percentage of cancelled targets compared to sham. Finally, the results revealed no left-right asymmetries in the visual imagery task, either after sham or anodal stimulation. The specific effect of parietal tDCS on the initiation of visual search offers a new perspective for targeted neurorehabilitation strategies and provides further insight into the different sensitivity of visual search measures classically used in brain-lesioned patients.